Autoantibodies in Morphea: An Update - Khatri, Sangita; Torok, Kathryn S.; Mirizio, Emily; Liu, Christopher; Astakhova, Kira (Frontiers in Immunology, 2019)
Skin autoimmune conditions belong to a larger group of connective tissue diseases and primarily affect the skin, but might also involve underlying tissues, such as fat tissue, muscle, and bone. Autoimmune antibodies (autoantibodies) play a role in autoimmune skin diseases, such as localized scleroderma also termed morphea, and systemic scleroderma, also called systemic sclerosis (SSc). The detailed studies on the biological role of autoantibodies in autoimmune skin diseases are limited. This results in a few available tools for effective diagnosis and management of autoimmune skin diseases. This review aims to provide an update on the detection and most recent research on autoantibodies in morphea. Several recent studies have indicated the association of autoantibody profiles with disease subtypes, damage extent, and relapse potential, opening up exciting new possibilities for personalized disease management. We discuss the role of existing autoantibody tests in morphea management and the most recent studies on morphea pathogenesis. We also provide an update on novel autoantibody biomarkers for the diagnosis and study of morphea.